Pengaruh Literasi Keuangan Terhadap Pola Pengelolaan Uang Saku Santri di Pondok Pesantren Raudhatul Ulum Kecamatan Sanggau Ledo Kabupaten Bengkayang - Roza, Riema; Firayanti, Yuni; Mahardhika, Tubagus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to determine the effect of financial literacy on the pocket money management patterns of santri (students) at the Raudhatul Ulum Islamic Boarding School, Sanggau Ledo District, Bengkayang Regency. This research applied a quantitative approach with a survey method. The population for this study consisted of all santri at the Raudhatul Ulum Islamic Boarding School, with a sample of 43 santri determined using the Slovin formula and a probability sampling technique. Data was collected through the distribution of questionnaires that used a Likert scale to measure the financial literacy variable (X) and the pocket money management pattern variable (Y). The data analysis techniques used included validity tests, reliability tests, classical assumption tests, and simple linear regression analysis to test the hypothesis. The results of the study indicate that financial literacy has a positive and significant effect on the santri's pocket money management patterns. This is statistically proven by the t-test results, which yielded a t-count of 4.542, greater than the t-table value (2.016), with a significance level of 0.000, which is lower than 0.05. The derived regression equation is Y = 11.428 + 0.553X. The conclusion of this research is that the higher the level of financial literacy possessed by the santri, the better and wiser their patterns of managing pocket money will be. An increase in financial understanding directly shapes better and wiser money management behavior among the santri at the Islamic boarding school.